Chorionic Villus Sampling (CVS) for Prenatal Diagnosis of Genetic Disorders in Bangladesh (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
Objective(s): The aim of the study was to identify safety and outcome of trans abdominal Chorionic Villus Sampling (CVS) for prenatal diagnosis of genetic disorders.Materials and methods: This is a retrospective analytical study on women who had undergone trans abdominal CVS. All CVS were done at Fetal medicine centre, Family Foundation, Green Road, Dhaka, from June 2013 to December 2016. A total of 286 couples, who were referred for prenatal diagnosis of various genetic disorders were studied. Trans abdominal CVS was done under local anesthesia and real-time ultrasound guidance. A 18G/88mm Spinal Needle (B Braun, Germany) was used. All CVS were performed with the 2 operators technique. The needle was introduced trans abdominally into the placenta in its longitudinal direction. Once the needle was adequately placed, the chorionic villi were aspirated with a to and fro jiggling movement of the aspiration needle and a suction force was applied through a syringe. Results were recorded and analyzed for descriptive statistics.Results: A total of 286 CVSs were performed as outdoor basis. The most common indication was detecting Beta-thalassaemia (82.5%). Other indications were for diagnosis of aneuploidy (9.7%), Hemophilia (3.1%), Spinal muscular atrophy (SMA) (2.4%), Duchenne Muscular Dystrophy (DMD) (2%). Most procedures were done between 11 and 13 weeks (range 11- 14 weeks). Most aspirations (95.1%) were easy; however, in 4.8% cases the aspiration was difficult due to a variety of factors. The overall success rate was 100%. Minor complications like placental hematoma and pervaginal (P/V) bleeding occurred in 2% and 1.3% respectively, which were subsided by conservative management. The procedure related miscarriage within three weeks not occurred in any cases.Conclusion: Trans abdominal CVS under real-time sonography is a useful outdoor procedure for prenatal diagnosis in early pregnancy without significant risk to the mother and the fetus.Bangladesh J Obstet Gynaecol, 2016; Vol. 31(2) : 63-69